P. Morgan Copt. 10 A Monastic Recipe for Healing Infertility - Willingham, Rochelle (2025)
The papyrus P. Morgan Copt. 10 contains a recipe for healing infertility, dating to approximately the seventh century CE, and has been associated with the Apa Apollo Monastery in Bawit, Egypt. The prayer - explicitly intended to be recited over a cup of wine - includes an initial address to God, a mention of the promise made to the matriarch Sarah, a series of divine titles of God, a formal request to loosen the woman's womb, and an appeal to God's name. This paper uses the recipe as a case study of monastic healing practices and to problematize the firm distinctions between such categories as medicine, magic, prayer, and liturgy.
Keywords: Egypt; Healing; historiola; Infertility; Late Antiquity; Monasticism